Meningkatkan Kemampuan Berfikir Logis Melalui Permainan Finding Treasure Pada Anak Usia 5-6 Tahun Di Raudhatul Athfal Al Hidayah Kecamatan Karangpawitan - Pratiwi, Shelly; Patonah, Putri (LP2M STAI Al-Musaddadiyah Garut, 2024)
This research is motivated by the understanding of logical thinking in group B RA Al Hidayah Garut for the 2023/2024 academic year which is still relatively low with a percentage of 90% of the total 18 children not understanding logical thinking. Among them, 7 children are not yet developing (BB), 5 children are starting to develop (MB), 4 children are developing according to expectations, and only 2 children are in the very well developing (BSB) category. This research aims to describe that using the finding treasure game method there is an increase in understanding of logical thinking in young children. The research method used is the classroom action research method (PTK) with the Kemmis MC and Taggart models. The research was carried out in three cycles and each cycle consisted of two meetings of planning, action, observation and reflection procedures. Data collection techniques in this research are through observation, interviews and documentation. The results of the research show that the improvement in children's logical thinking increases with each cycle. So it can be concluded that using the finding treasure game method can improve the logical thinking abilities of young children in group B at RA Al Hidayah Garut. This was marked by an increase in the percentage of children's success, which was initially 33.3%, increased in cycle I to 55.5%, cycle II increased to 88.9%, and cycle III to 94.4%. Keywords : Logical Thinking; finding Treasure; Early Chidhood Education